Protective Measures to Enhance Human Longevity and Aging: A Review of Strategies to Minimize Cellular Damage - Umesh C. Gupta; Subhas C. Gupta (Journal of Basic & Applied Sciences, 2019)
Aging is a universal process in all life forms. The most current and widely accepted definition of human aging is a progressive loss of function and energy production that is accompanied by decreased fertility and increased mortality with advancing age. The most obvious and commonly recognized consequence of aging and energy decline is a decrease in skeletal muscle function, which affects every aspect of human life from the ability to walk and run, to chew, and swallow and digest food. Some crucial factors responsible for aging and longevity include genetics, environment, and nutrition, serious disease disorders such as cancer and cardio-vascular diseases, sarcoma and cell senescence. Oxidative damage caused due to the accumulation of molecular waste-by-products of the body’s metabolic processes, which our bodies are unable to break down or excrete, is chiefly responsible for aging and diseases. Regular physical activity, consumption of foods rich in phytochemicals and anti-oxidants, cessation of smoking, avoiding foods high in saturated and hydrogenated fats are some of the strategies that should be taken into account to delay aging and prolong longevity.